Direct Methods for Limit and Shakedown Analysis of Structures (Advanced Computational Algorithms and Material Modelling) - Fuschi, Paolo (Springer, 2015)
Over the last decades powerful numerical methods have been developed to carry out one of the oldest and most important tasks of design engineers, which is to determine the load carrying capacity of structures and structural elements. Partic ularly attractive among these methods are the so-called “Direct Methods”, embracing Limit—and Shakedown Analysis because they allow rapid and direct access to the requested information in mathematically constructive manners without cumbersome step-by-step computation...